The Influence of Relationship Marketing on Customer Loyalty of Glad2Glow Skincare Products in Medan - Azzahra, Nindya; Rini, Endang Sulistya; Fawzea, Beby Karina (CV Raskha Media Group, 2025)
This study examines the influence of relationship marketing on customer loyalty toward Glad2Glow skincare products in Medan. Relationship marketing is operationalized through trust, commitment, communication, and personalized service; customer loyalty is measured by repurchase intention, positive word-of-mouth, and brand preference. Using a cross-sectional survey of 320 Glad2Glow customers in Medan and analyzed with partial least squares structural equation modeling (PLS-SEM), the study finds that trust and commitment significantly predict customer loyalty, while communication and personalization show moderate but positive effects. The research contributes to both theory and practice by validating relationship marketing dimensions in an Indonesian skincare retail context and offering managerial recommendations to strengthen loyalty through targeted relationship-building strategies.